Capabilities for value co-creation and value capture in emergent platform ecosystems: A longitudinal case study of SAP's cloud platform. (December 2021) - Schreieck, Maximilian; Wiesche, Manuel; Krcmar, Helmut
Companies across industries are shifting toward a platform ecosystem strategy. By leveraging cloud computing technologies, companies aim to benefit from collaboration with a wide range of third-party developers within emergent platform ecosystems. To succeed, these companies need to develop new organizational capabilities to co-create and capture value in platform ecosystems. To understand what capabilities are crucial to establish platform ecosystems and how they contribute to value co-creation and value capture, we conducted a multi-year, in-depth case study of SAP's cloud platform project. We identified (1) technology-related capabilities (cloud-based platformization, open IT landscape management) and (2) relationship-driven capabilities (ecosystem orchestration, platform evangelism, platform co-selling) and illustrate how these capabilities help the platform owner to enable and balance value co-creation and value capture in an emergent platform ecosystem. With our findings, we contribute to the discussion on how companies can overcome the challenging emergent phase of platform ecosystems. We thereby bridge literature on value creation in platform ecosystems and on organizational capabilities. Though we conducted our study in the context of the enterprise software industry, we discuss how our findings apply to prospective platform owners from different contexts.